The handbook of energy trading - Fiorenzani, Stefano (Wiley finance series., 2012)
"This book guides readers through all the various aspects of energy trading from operational strategies and mathematical methods to practical techniques, providing support for energy trading managers, energy traders and energy trading analysts"--